Joint production and human replacement optimization policy for a deteriorating manufacturing system - Hanan Majria; Honorine Angue Mintsa, Guy-Richard Kibouka; Jean-Pierre Kenne (Universitas Ahmad Dahlan, 2025)
This article examines the integration of production and human resource and human resource management, considering the operator as a production unit whose efficiency decreases over time, in an unreliable production system marked by significant deterioration. This deterioration impacts the reliability and continuity of the production unit in two main ways. To mitigate the impact of this deterioration, a replacement action can be implemented based on the system's current state. The objective of this study is to establish an effective production policy and replacement strategy to meet customer demand. We employ a combination of stochastic dynamic programming and numerical methods to solve this optimal control problem. Additionally, a numerical example is presented to demonstrate the applicability of the proposed approach and to explore the interaction between a specific production strategy and human resource management. The main contribution of this research lies in the development of innovative methods and solutions aimed at optimizing the performance of a complex system through stochastic optimal control. The impact of the new approach, based on a logical implementation, is discussed following a sensitivity analysis of the numerical example. The results include a comparative study between recent research and the proposed policy. Lastly, an implementation chart is created to assist decision-makers in determining production rates and managing human resources effectively to meet customer demand.